2021
DOI: 10.1016/j.toxcx.2021.100075
|View full text |Cite
|
Sign up to set email alerts
|

Snakebite incidents, prevention and care during COVID-19: Global key-informant experiences

Abstract: Snakebite envenoming is a long-neglected disease causing significant morbidity and mortality in snakebite endemic low- and middle-income countries (LMICs). Global awareness on snakebite was increasing steadily up to 2020, and an increasing number of countries began to acknowledge the issue, when coronavirus disease 2019 (COVID-19) started to have an unprecedented impact on societies and health systems. To better understand how snakebite incidents, prevention and care are being affected during this global emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
10
1
1
Order By: Relevance
“…Fourth, impact of the coronavirus disease 2019 (COVID-19) pandemic on snakebite and antivenom situation in ASEAN countries was not included during the interviews. However, the overall economic burden of COVID-19 pandemic on ASEAN countries would most likely worsen access to antivenom due to financial constraints at least for some countries, as previously investigated by van Oirschot and colleagues 36. Lastly, most findings were based on interviews because the included studies were mostly limited to epidemiological aspects of snakebite rather than access to antivenoms.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, impact of the coronavirus disease 2019 (COVID-19) pandemic on snakebite and antivenom situation in ASEAN countries was not included during the interviews. However, the overall economic burden of COVID-19 pandemic on ASEAN countries would most likely worsen access to antivenom due to financial constraints at least for some countries, as previously investigated by van Oirschot and colleagues 36. Lastly, most findings were based on interviews because the included studies were mostly limited to epidemiological aspects of snakebite rather than access to antivenoms.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding natural disasters and snakebite, other informants surveyed in the study, Van Oirschot et al reported that they had seen an increase in snakebite cases but did not directly relate this to COVID-19 ( van Oirschot et al, 2021 ). Instead they associated it to” increased rainfall or flood” (Bangladesh, Malaysia, Nepal, Brazil).…”
Section: Resultsmentioning
confidence: 90%
“…Our search was completed by non-peer reviewed publications suggested by key-informants or found outside the systematic search. Firstly, we included a large peer-reviewed study published in Toxicon-X recently that expressed the views of experts and key-informants about the impact of the global COVID-19 pandemic and crisis on the burden of snakebite ( van Oirschot et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The strategy was tasked by the Snakebite Envenoming Working Group (SBE-WG) concentrating on the achievement of a 50% reduction in mortality and disability caused by snakebite envenoming by 2030. This aim will be accomplished through four objectives in terms of engagement of the communities, provision of safe effective treatment, strengthening of the health systems and establishment of an effective partnership [9].…”
Section: Discussionmentioning
confidence: 99%